Shoulder impingement syndrome: Outcome of arthroscopic subacromial decompression in Kuantan - Mat Lani, Muhammad Taufik; Siron @ Baharom, Khairul Nizam (Malaysian Orthopaedic Association (MOA), 2018)
INTRODUCTION: Shoulder impingement syndrome is one of the common problem which leads to shoulder disabilities. Neer (1972) first to describe this condition as impingement to the rotator cuff by anterior third of the acromion process. Treatment options varies depending on grade of the impingement and rotator cuff involvement. Arthroscopic subacromial decompression (ASAD) has become more popular in recent years and have shown to have good outcomes. MATERIALS & METHODS: Patients who underwent ASAD with or without rotator cuff repair in Hospital Tengku Ampuan Afzan, Kuantan and International Islamic University Medical Centre Kuantan from September 2016 until Dec 2017 were studied. The functional outcomes were evaluated using ASES, DASH and Constant scoring system. The patients were assessed at preoperative, 3months and 6 months post ASAD. RESULTS: 10 patients were collected. 2 patients also underwent ACJ resection, 2 patients with rotator cuff repair and another 1 converted to mini open cuff repair. All patients are satisfied with their current functions and have showed good functional outcome as early as 3 months. Mean constant score at 3 months is fair (25) but at 6 months is excellent (<11). Mean ASES and DASH score showed improvement by 72% and 56% respectively at 3 months compared to preoperative condition. While at 6 months improved by 86% and 74% respectively. DISCUSSIONS: Surgical treatment is always indicated if conservative treatment failed. Options of arthroscopic or mini open with or without rotator cuff repair remains debatable. Both have shown good outcome in terms of function and study showed there were no significant different [1]. In recent years, however, arthroscopic surgery became more popular compared to mini open as it is less invasive and proven to have good outcomes in short and long term [2][3]. Bidwai et al (2015) concluded that there is no significant benefit of cuff repair over decompression alone in partial cuff tear. Even though ASAD has proven good functional outcomes and has become more popular, it is still inconclusive whether is it the best treatment option in managing shoulder impingement syndrome. CONCLUSION: Arthroscopic subacromial decompression does give a good functional outcome in treating shoulder impingement syndrome with or without rotator cuff tear.